Peningkatan Kemampuan Mengemukakan Pendapat Melalui Model Pembelajaran Group Investigation (GI) pada Mata Pelajaran PKN - Abdullah Fatah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This study aims to improve students’ ability to express opinions through the implementation of the Group Investigation (GI) learning model in Civics Education (PKn) for fifth-grade students at MI Darul Ulum Sarirejo. The study employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The research subjects were 12 students consisting of 7 male and 5 female students. Data collection techniques included observation, tests, and documentation, while data analysis used descriptive quantitative analysis by calculating students’ learning completeness percentages. The results showed that the implementation of the Group Investigation learning model was able to improve students’ ability to express opinions. In the initial condition, the learning completeness percentage was only 33%, then increased to 58% in cycle I and reached 75% in cycle II. The application of the Group Investigation model also increased students’ activeness, self-confidence, critical thinking skills, and social interaction during the learning process. Thus, the Group Investigation learning model is effective in improving students’ ability to express opinions in Civics learning for fifth-grade students at MI Darul Ulum Sarirejo